2007
DOI: 10.1128/aem.00704-07
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lactic Acid Bacteria on Longevity ofCaenorhabditis elegansand Host Defense againstSalmonella entericaSerovar Enteritidis

Abstract: This study aimed to develop a convenient model to investigate the senescence of host defenses and the influence of food and nutrition. A small soil nematode, Caenorhabditis elegans, was grown for 3 days from hatching on a lawn of Escherichia coli OP50 as the normal food source, and subsequently some of the nematodes were fed lactic acid bacteria (LAB). The life spans of worms fed LAB were significantly longer than the life spans of those fed OP50. To investigate the effect of age on host defenses, 3-to 7-day-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
148
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(169 citation statements)
references
References 41 publications
13
148
0
2
Order By: Relevance
“…Feeding of L. rhamnosus R4 has effectively increased the mean lifespan of C. elegans, and the life extension rate reached a maximum of 36.1%. This is in accordance with the results described by Ikeda et al (2007), in which feeding nematodes with bifidobacteria or lactobacilli caused increased average lifespans compared to those fed with OP50 and the life extension rates ranged from 17% to 33%. These results suggested that different strains show diverse impacts on lifespan extension.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Feeding of L. rhamnosus R4 has effectively increased the mean lifespan of C. elegans, and the life extension rate reached a maximum of 36.1%. This is in accordance with the results described by Ikeda et al (2007), in which feeding nematodes with bifidobacteria or lactobacilli caused increased average lifespans compared to those fed with OP50 and the life extension rates ranged from 17% to 33%. These results suggested that different strains show diverse impacts on lifespan extension.…”
Section: Discussionsupporting
confidence: 81%
“…The effect of selected LAB strains on longevity in C. elegans was examined using the killing assay as described by Ikeda et al (2007), with slight modifications. Briefly, the synchronized worms were grown at 20 °C until they reached L4 stage.…”
Section: Elegans Killing Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Ikeda et al . (2007) have also studied the effects of different probiotic strains in C. elegans , including Bifidobacterium , Lactobacillus helveticus , and Lactobacillus plantarum . Immune‐stimulating molecules, such as peptidoglycan (Lebeer et al ., 2010), S‐layer protein (Konstantinov et al ., 2008), and exopolysaccharide (Kim & Kim, 2009; Kim et al ., 2010) exist on the cell surfaces of these bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…elegans is useful for studying the relationship between innate immunity and pathogens because the nematode lacks an adaptive immune system. Using the worms on agar plates containing no bacterial nutrients, we recently found that lactic acid bacteria can enhance the host's defense against salmonella in C. elegans and prolong lifespan 13) . Although C. elegans does not have phagocytes specialized for innate host defense, it produces a variety of humoral antibiotic substances such as lysozymes, caenopores, lipase, lectins and C3-like thioester-containing proteins, and defensin-like antibiotic peptides 1,18,20,25,26) .…”
Section: Discussionmentioning
confidence: 99%